Comparative Study of the West African Continental, Coastal, and Marine Atmospheric Profiles during the Summer of 2006 - Ibrahima Kalil Kante; Daouda Badiane; Saïdou Moustapha Sall; Abdoulaye Deme; Arona Diedhiou (International Journal of Geophysics)
We used sounding data of the Multidisciplinary Analysis of the African Monsoon experience in summer 2006 at continental and coastal sites of West Africa, respectively, to analyze the vertical profiles of relative humidity, temperature, dew point, and speed and wind direction for the JJAS rainy period. The vertical gradient method is applied to the profiles of some thermodynamic parameters estimated from sounding data to do a comparative study of the structure and thermal properties, moisture, and static stability of the atmospheric boundary layer of inland, coastal, and marine sites to show consistent differences related to geographic factors. In vertical profiles of relative humidity, the intensity is higher in Dakar than in Niamey particularly in the core of the season. There are dry intrusions in the low levels at the beginning and end of the season in Dakar, which do not exist in Niamey. The mixing layer on the continent during the day can reach a height greater than 1100 m, and the inversion layer height can exceed 1700 m. Therefore, the maximum thickness of the boundary layer is observed on the continent during the day, while at night the marine boundary layer is the thickest. The diurnal evolution shows that the mixing layer thickness decreases during the night over the continent but increases at the coast and at sea. In the night at the continental site there is a division of the mixing layer with a consistent residual mixing layer. Continental boundary layer is more unstable during the day, while at night it is the marine boundary layer that is more unstable than the coastal and inland ones.